EFFECT OF COMBINATION DOSES OF NITROGEN, PHOSPHOR, AND POTASSIUM FERTILIZER ON THE PRODUCTIVITY OF Indigofera zollingeriana PLANTS - ., Sanusi; Trisnadewi, A.A.A.S.; Duarsa, M.A.P. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
One way to overcome limited forage is to use the legume plant Indigofera zollingeriana . Effort to increase the growth and yield of Indigofera zollingeriana plants, it is necessary to apply fertilizer at the right dose to meet the required nutrients, such as providing a combination of nitrogen (N), phosphorus (P) and potassium (K) fertilizers. This research aims to determine the effect of a combination of nitrogen, phosphorus and potassium fertilizers at different doses on the growth and yield of Indigofera zollingeriana plants. This research was carried out at the Sesetan Research Station, Faculty of Animal Husbandry, Udayana University for 10 weeks. This research used a completely randomized design (CRD) with 5 treatments and 6 replications, so there were 30 experimental units. Treatment consists of P0 (0 kg urea ha -1   + 0 kg SP 36 ha -1 + 0 kg KCL ha -1 ), P1 (50 kg urea ha -1 + 50 kg SP 36 ha -1 + 50 kg KCL ha -1 ), P2 (50 kg urea ha -1 + 100 kg SP 36 ha -1 SP + 100 kg KCL ha -1 ) , P3 (50 kg urea ha -1 + 150 kg SP 36 ha -1 + 150 kg KCL ha -1 ), P4 (50 kg urea ha -1 + 200 kg SP 36 ha -1 + 200 kg KCL ha -1 ). The variables observed in this research include growth variables, results and growth characteristic variables. The results showed that giving a combination of N, P and K fertilizer doses to Indigofera zollingeriana plants did not show significant differences in all observed variables. Giving (50 kg urea ha -1 + 200 kg SP 36 ha -1 + 200 kg KCL ha -1 ) treatment tends to provide better growth and yield responses than other treatments. It can be concluded that giving a combination of N, P and K fertilizers at different doses to Indigofera zollingeriana plants has not been able to increase the growth and yield of Indigofera zollingeriana plants.